2012
DOI: 10.1523/jneurosci.0397-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Receptors Enable the Transport of Rapsyn from the Golgi Complex to the Plasma Membrane

Abstract: The accumulation of acetylcholine receptors (AChRs) at nerve terminals is critical for signal transmission at the neuromuscular junction, and rapsyn is essential for this process. Previous studies suggest that AChRs might direct rapsyn self-clusters to the synapse. In vivo experiments with fluorescently tagged AChR or rapsyn in zebrafish larvae revealed that rapsyn self-clusters separate from AChRs did not exist before synapse formation. Examination of rapsyn in the AChR-less mutant sofa potato revealed that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The primary antibodies used were: rabbit anti-Mdka 1:200 (Zymed Laboratories-Invitrogen; see [ 49 ]), mouse anti-BrdU 1:100 (BD Biosciences 347580), mouse anti-GM130 1:200 (BD Biosciences 610822; [ 50 ]), mouse anti-Glutamine Synthetase 1:200 (Millipore MAB302), mouse anti-GFP 1:200 (Millipore MAB3580), mouse anti-Zpr1 1:200 (anti-Arrestin 3, ZIRC), mouse anti-Zpr3 1:200 (anti-Rhodopsin, ZIRC). Secondary antibodies (Invitrogen) were raised against in either mouse or rabbit antibodies and conjugated to Alexa Fluor 488 and 555 and diluted 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…The primary antibodies used were: rabbit anti-Mdka 1:200 (Zymed Laboratories-Invitrogen; see [ 49 ]), mouse anti-BrdU 1:100 (BD Biosciences 347580), mouse anti-GM130 1:200 (BD Biosciences 610822; [ 50 ]), mouse anti-Glutamine Synthetase 1:200 (Millipore MAB302), mouse anti-GFP 1:200 (Millipore MAB3580), mouse anti-Zpr1 1:200 (anti-Arrestin 3, ZIRC), mouse anti-Zpr3 1:200 (anti-Rhodopsin, ZIRC). Secondary antibodies (Invitrogen) were raised against in either mouse or rabbit antibodies and conjugated to Alexa Fluor 488 and 555 and diluted 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…One notable feature of the zebrafish NMJ is its accessibility for optical, time-lapse studies in vivo. Ex-utero development combined with genetically introduced fluorescent molecules enable studies in which synapse formation can be observed in its entirety, both spatially and temporally [ 14 , 41 , 42 ]. Studies utilizing these unique approaches complement studies using human patients or mammalian animal models.…”
Section: Discussionmentioning
confidence: 99%
“…However a conserved leucine residue is changed to proline near the N-terminus, which blocks the assembly of pentamers. In nic and sofa potato , AChR pentamers fail to form and the remaining normal subunits are retained in the endoplasmic reticulum [ 14 ]. These null mutants are completely paralyzed until their death approximately 7 days post-fertilization (dpf), but can be rescued by introducing a normal copy of the mutant subunit [ 13 , 15 ].…”
Section: Mutants Of Achr Subunitsmentioning
confidence: 99%
See 2 more Smart Citations